Examining the resilience of mobile youth in KwaZulu-Natal, South Africa: a qualitative inquiry through the lens of protection and risk - Nothando Ngwenya; Sarah Bernays; Nondumiso Dlamini; Maryam Shahmanesh; Janet Seeley (BMC Public Health)
Abstract Background The last few decades have seen a demographic shift in the age of migrants with more young people involved, especially with regards to internal migration. Socio-economic deprivation, limited resources and adversities contribute to many young people leaving rural areas in low- and middle-income countries in search of a better life in urban settings. This move often requires an adaptation process and resilience to the adversities young people face while still in the challenging developmental life stage of adolescence, exposing them to health and physical risks. Methods As part of Lending a Hand support intervention, we conducted repeat in-depth interviews with 20 young people that had recently relocated from other rural villages to a peri-urban setting in uMkhanyakude district, KwaZulu-Natal in South Africa. Data were analysed thematically using inductive and deductive approaches and managed in NVivo software. Results The participants shared that there were alarming rates of teenage pregnancies in their local area and attributed this to younger girls dating older men for economic gain, which also exposed them to infectious diseases. Some vulnerabilities described by young people included coming from a single parent home, experiencing psychological distress, and living far away from the support of family. Other young people were able to use community-based resources as well as adaptive emotion regulation strategies that offered protective support such as church, school, and peer networks around them. Conclusions The accessibility and availability of protective resources offered support and provided strength to young people. This fostered resilience for these young people and in a way incorporated aspects of the collectivist communities they live in. Considering resources that are easily available in resource limited settings is important as young people may be more comfortable and confident to access and use. These protective factors may help curb some of the impact of the risks that they are exposed to.